Radiochimica Acta : International Journal for chemical aspects of nuclear science and technology (Oldenbourg Wissenschaftsverlag, 1962)
Radiochimica Acta publishes original papers, review articles, and "rapid communications" (short articles of a more timely interest) on all chemical aspects of nuclear science and technology. The journal is geared toward scientists who are actively engaged in research work.